The Quantile Effects of Climate and Global Economic Policy Uncertainties on Renewable Energy Demands in the BRICS Nations: The Role of Green Ecological Policies - Dima AlAyoubi; Tarik Atan; Majdi Awad (Energies)
Renewable energy has an important role in attaining environmental quality. Numerous studies have determined the factors driving the diminishment or promotion of renewable energy consumption (REC) globally. Despite the findings of prior studies, the specific effects of climate policy uncertainty (CPU) and global economic policy uncertainty (GEPU) on REC have not been probed in the case of BRICS economies. Furthermore, fewer considerations have been taken into account to explore whether green environmental policies (EPs) have a moderating role. Therefore, the present work contributes to filling the gap by providing an empirical model and assessing the panel quantile data and fixed-effect methods used between 2010 and 2020. The findings reveal that the expansion of the financial market, inflowing FDI, rising international remittances, developing environmental innovation, and increasing CPU are significant factors promoting REC while unfavorably increasing CO2, economic activity, and GEPU impact. Notably, the results underscore that EPs have a significant positive effect, and stricter ecological strategies lead to a rise in REC. In addition, the findings highlight that by implementing stricter EPs, the effect of CPU on REC becomes more positive, and the negative effect of GEPU on REC is more controlled. In particular, the significant interaction effects highlight that the beneficial role of EPs is more pronounced in nations with strong EPs relative to low EPs. Overall, EPs have a substantial beneficial role in promoting REC when CPU and GEPU arise. These findings are reliable after using numerous measurements and methods, and several policy recommendations are suggested to governments, policymakers, and regulatory bodies.